Perforasi pada Penderita Apendisitis Di RSUD DR.H.Abdul Moeloek Lampung - Mizar Erianto; Neno Fitriyani; Andi Siswandi; Arya Putri Sukulima (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Background: Perforation appendicitis is the most common cause of appendix pain and requires immediate major surgery to prevent complications that are generally dangerous. this disease can affect all ages, but which often strikes ages between 20-30 years. Furthermore, the condition of acute appendicitis increases the risk of perforation and formation of the periapendicular period. Perforations with inflammatory fluid and bacteria enter the abdominal cavity and then respond to the peritoneal surface inflammation or peritonitis. The incidence of appendicitis in Indonesia in 2014 showed the number of appendicitis treated at the hospital as many as 4,351 cases. Objective: To find out the description of appendicitis perforation sufferers in adults with acute appendicitis at the Regional General Hospital Dr. H. Abdul Moeloek Lampung Province in 2017. Methods: Type of quantitative research, descriptive design. The entire population of all patients with adult acute appendicitis was 151 people. A sample of 110 people with random sampling techniques.Retrieval of data using observation sheet medical record data.Data analysis techniques using Univariate statistical tests.Results: The frequency distribution of the age of appendicitis perforated patients, most of them were aged 20-30 years as many as 48 patients (43.63%). The frequency distribution of the sex of patients with appendicitis perforation, most of them were male as many as 92 patients (83.63%). The frequency distribution of body temperature of patients with appendicitis perforation, mostly with body temperature> 37.5 ° C as many as 103 patients (93.63%). The frequency distribution of leukocyte levels of appendicitis perforated patients, mostly with leukocyte levels> 18,000 / mm as many as 84 patients (76.36%).